Evaluation of Subcision for the Correction of the Prominent Nasolabial Folds - R. M. Robati; F. Abdollahimajd; A. M. Robati (Hindawi Limited, 2015)
Background. A prominent nasolabial fold (NLF) is a cosmetic problem. Currently, numerous therapeutic modalities are available for pronounced NLFs with variable efficacy. Objective. To determine the efficacy and safety of subcision using a hypodermic needle for the correction of the prominent NLFs and its effect on skin elasticity. Methods. Sixteen patients with prominent NLFs underwent subcision. The investigators' assessment of improvement and the patients' satisfaction were both recorded 1 and 6 months after the procedure. Also, we evaluate the skin elasticity of NLFs before and after the treatment using a sensitive biometrologic device with the measurement of cutaneous resonance running time (CRRT). Results. Thirteen (81.25%) patients showed a moderate improvement at 1st month and 13 (81.25%) patients had at least a mild improvement at 6th month. There was no persistent side effect lasting more than a few days. Mean CRRT at 1 and 6 months after the treatment was significantly higher compared to the baseline. Conclusion. Subcision may be considered effective for the correction of pronounced NLFs. However, further controlled studies with larger sample size are necessary to assess the efficacy of this technique in particular with use of more objective assessment of skin biometric characteristics. This trial is registered with IRCT201108097270N1 (registered on January 27, 2012).